Relationship between endothelium-dependent vasodilation and fat distribution using the new “imiomics” image analysis technique - Lind, Lars; Strand, Robin; Michaelsson, Karl; Kullberg, Joel; Ahlström, Håkan (Nutrition, metabolism, and cardiovascular diseases, 2019)
We investigated how vasoreactivity in the brachial artery and the forearm resistance vessels were related to fat distribution and tissue volume, using both traditional imaging analysis and a new technique, called “Imiomics”, whereby vasoreactivity was related to each of the >2M 3D image elements included in the whole-body magnetic resonance imaging (MRI). In 326 subjects in the Prospective investigation of Obesity, Energy and Metabolism (POEM) study (all aged 50 years), endothelium-dependent vasodilation was measured by acetylcholine infusion in the brachial artery (EDV) and flow-mediated vasodilation (FMD). Fat distribution was evaluated by dual-energy X-ray absorptiometry (DXA) and magnetic resonance imaging (MRI). EDV, but not FMD, was significantly related to total fat mass, liver fat, subcutaneous (SAT) and visceral (VAT) adipose tissue in a negative fashion in women, but not in men. Using Imiomics, an inverse relationship was seen between EDV and a local tissue volume of SAT in both the upper part of the body, as well as the gluteo-femoral part and the medial parts of the legs in women. Also the size of the liver, heart and VAT was inversely related to EDV. In men, less pronounced relationships were seen. FMD was also significantly related to local tissue volume of upper-body SAT and liver fat in women, but less so in men. EDV, and to a lesser degree also FMD, were related to liver fat, SAT and VAT in women, but less so in men. Imiomics both confirmed findings from traditional methods and resulted in new, more detailed results. •EDV and to a lesser degree FMV are related to liver fat, subcutaneous and visceral fat in women.•Imiomics both confirmed findings from traditional methods and resulted in more detailed results.•An inverse relationship is seen between EDV and SAT in the upper part of the body in women.•An inverse relationship is seen between EDV and SAT in the gluteo-femoral parts of the legs in women.•In men, less pronounced relationships were seen.